Effects of Age and Sex on Clinical Outcomes After Percutaneous Coronary Intervention Relative to Coronary Artery Bypass Grafting in Patients With Triple-Vessel Coronary Artery Disease. Issue 19 (10th May 2016) - Yamaji, Kyohei; Shiomi, Hiroki; Morimoto, Takeshi; Nakatsuma, Kenji; Toyota, Toshiaki; Ono, Koh; Furukawa, Yutaka; Nakagawa, Yoshihisa; Kadota, Kazushige; Ando, Kenji; Shirai, Shinichi; Onodera, Tomoya; et al.
Abstract : Background—: Age and sex are important considerations in the choice between percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) in daily clinical practice. Methods and Results—: Of 25 816 patients enrolled in the multicenter Coronary Revascularization Demonstrating Outcome Study in Kyoto (CREDO-Kyoto; Cohort-1, n=9877; Cohort-2, n=15 939), the present study population consisted of 5651 patients (men, n=3998; women, n=1653) with triple-vessel coronary artery disease who were considered to be pertinent in comparisons of PCI with CABG (PCI, n=3165; CABG, n=2486). Patients were divided into 3 groups according to the tertiles of age: ⩽65 years (n=1972), 66 to 73 years (n=1820), and ≥74 years (n=1859). The excess adjusted mortality risk of PCI relative to CABG was significant in patients ≥74 years of age (hazard ratio [HR], 1.40; 95% confidence interval [CI], 1.10–1.79; P =0.006), whereas the risks were neutral in patients ⩽65 years of age (HR, 1.05; 95% CI, 0.73–1.53; P =0.78) and in patients 66 to 73 years of age (HR, 1.03; 95% CI, 0.78–1.36; P =0.85; interaction P =0.003). The excess mortality risk of PCI relative to CABG was significant in men (HR, 1.24; 95% CI, 1.03–1.50; P =0.02) and trended to be significant in women (HR, 1.34; 95% CI, 0.98–1.84; P =0.07) without significant interaction between sex and the mortality risk of PCI relative to CABG (interaction P =0.40). Conclusions—: There was a significant association between age and the mortality risk of PCI relative to CABG with excess risk in patients ≥74 years of age and neutral risk in younger patients. There was no significant sex-related difference in the mortality risk of PCI relative to CABG. Abstract : Supplemental Digital Content is available in the text.